Authoritarianism and support for Trump in the 2016 presidential election. Issue 1 (2nd January 2022) - Knuckey, Jonathan; Hassan, Komysha
ABSTRACT: The emergence of authoritarianism as a core political value has been emphasized by recent scholarship on the political behavior of the American electorate. This paper adds to this literature by examining the effect of authoritarianism in the 2016 U.S. presidential election. Given the campaign style of Trump and the issues that he made salient in his campaign, it is hypothesized that authoritarianism should have a substantial effect on vote choice of whites. Using data from the American National Election Studies (ANES), logistic regression models of presidential vote choice of white respondents are estimated to ascertain the effect of authoritarianism in presidential elections from 1992 to 2016, controlling for party identification, ideology and several standard demographic control variables. Findings indicate that authoritarianism had the largest effect on white vote choice in 2016 than in any prior election that was analyzed. The candidacy of Trump appears to have been the triggering mechanism given that authoritarianism was a less salient predictor of U.S. House vote choice in 2016. Moreover, this relationship was true for both college and non-college educated whites. Authoritarianism also seems to have been primed by Trump appealing to racial animus, anti-immigration sentiment, nativism, and anti-Muslim prejudice. Authoritarianism is likely to remain a salient determinant of vote choice during the Trump era. Indeed, a widening and deepening of this cleavage means its effects are likely to be apparent in elections below the presidency.